Storm chaser - Platt, Chris 1959- (Peachtree, 2009)
When a fire forces her family to turn their home into a guest ranch, aspiring horse trainer Jessica finds herself working once again with her favorite horse, Storm Chaser, to tame the wild filly for snobbish, spoiled Ariel, Storm Chaser's future owner.